Predicted class-I aminoacyl tRNA synthetase-like proteins in non-ribosomal peptide synthesis - Iyer Lakshminarayan M; de Souza Robson F; Aravind L (Biology Direct, 2010)
Abstract Background Recent studies point to a great diversity of non-ribosomal peptide synthesis systems with major roles in amino acid and co-factor biosynthesis, secondary metabolism, and post-translational modifications of proteins by peptide tags. The least studied of these systems are those utilizing tRNAs or aminoacyl-tRNA synthetases (AAtRS) in non-ribosomal peptide ligation. Results Here we describe novel examples of AAtRS related proteins that are likely to be involved in the synthesis of widely distributed peptide-derived metabolites. Using sensitive sequence profile methods we show that the cyclodipeptide synthases (CDPSs) are members of the HUP class of Rossmannoid domains and are likely to be highly derived versions of the class-I AAtRS catalytic domains. We also identify the first eukaryotic CDPSs in fungi and in animals; they might be involved in immune response in the latter organisms. We also identify a paralogous version of the methionyl-tRNA synthetase, which is widespread in bacteria, and present evidence using contextual information that it might function independently of protein synthesis as a peptide ligase in the formation of a peptide- derived secondary metabolite. This metabolite is likely to be heavily modified through multiple reactions catalyzed by a metal-binding cupin domain and a lysine N6 monooxygenase that are strictly associated with this paralogous methionyl-tRNA synthetase (MtRS). We further identify an analogous system wherein the MtRS has been replaced by more typical peptide ligases with the ATP-grasp or modular condensation-domains. Conclusions The prevalence of these predicted biosynthetic pathways in phylogenetically distant, pathogenic or symbiotic bacteria suggests that metabolites synthesized by them might participate in interactions with the host. More generally, these findings point to a complete spectrum of recruitment of AAtRS to various non-ribosomal biosynthetic pathways, ranging from the conventional AAtRS, through closely related paralogous AAtRS dedicated to certain pathways, to highly derived versions of the class-I AAtRS catalytic domain like the CDPSs. Both the conventional AAtRS and their closely related paralogs often provide aminoacylated tRNAs for peptide ligations by MprF/Fem/MurM-type acetyltransferase fold ligases in the synthesis of peptidoglycan, N-end rule modifications of proteins, lipid aminoacylation or biosynthesis of antibiotics, such as valinamycin. Alternatively they might supply aminoacylated tRNAs for other biosynthetic pathways like that for tetrapyrrole or directly function as peptide ligases as in the case of mycothiol and those identified here. Reviewers This article was reviewed by Andrei Osterman and Igor Zhulin.